Penerapan Model Pembelajaran Blended Learning dalam Meningkatkan Kemandirian dan Hasil Belajar IPS Siswa - Widiarti Iswandari (Journal of Profession Education, 2021)
The purpose of this study is to increase independence and social studies learning outcomes through the implementation of the Blended Learning learning model to students. The research subjects were 24 students of Class IX A SMP. The method used in this research is a classroom action research method which is carried out in 2 cycles through 4 stages, namely (1) planning, (2) implementation, (3) observation, (4) reflection. In the implementation of classroom action research using observation sheets and learning outcomes tests. Data analysis used comparative descriptive analysis technique. The results of this classroom action research indicate that the application of the Blended Learning learning model can increase students' independence and social studies learning outcomes.